CD44s-activated tPA/LRP1-NFκB pathway drives lamellipodia outgrowth in luminal-type breast cancer cells - Qiu, Yaqi; Wang, Hui; Guo, Qian; Liu, Yiwen; He, Yiqing; Zhang, Guoliang; Yang, Cuixia; Du, Yan; Gao, Feng (Frontiers in Cell and Developmental Biology, 2023)
Some cancer cells migration and metastasis are characterized by the outgrowth of lamellipodia protrusions in which the underlying mechanism remains unclear. Evidence has confirmed that lamellipodia formation could be regulated by various adhesion molecules, such as CD44, and we previously reported that lamellipodia at the leading edge of luminal type breast cancer (BrCa) were enriched with high expression of CD44. In this study, we found that the overexpression of CD44s could promote lamellipodia formation in BrCa cells through inducing tissue type plasminogen activator (tPA) upregulation, which was achieved by PI3K/Akt signaling pathway activation. Moreover, we revealed that tPA could interact with LDL receptor related protein 1 (LRP1) to activate the downstream NFκB signaling pathway, which in turn facilitate lamellipodia formation. Notably, inhibition of the tPA/LRP1-NFkB signaling cascade could attenuate the CD44s-induced lamellipodia formation. Thus, our findings uncover a novel role of CD44s in driving lamellipodia outgrowth through tPA/LRP1-NFkB axis in luminal BrCa cells that may be helpful for seeking potential therapeutic targets.